Assesment of Ips typographus attacks in relation to site and stand characteristics in managed andunmanaged oriental spruce (Picea orientalis (L.) Link) stands - Sarıyıldız, Temel; Duman, Ahmet (My University, 2020)
This study aimed at investigating the effectiveness of management practices for reducing the negative impacts of Ips typographus L. on Oriental spruce (Picea orientalis (L.) Link.) forests, and to review the best site factor(s) associated with Ips typographus infestation. Two sites, Hatila Valley National Park (HVNP-unmanaged site) and Saçinka Forest Sub-District Directorate (SFSD-managed site) were chosen to compare the stand characteristics (mean age, height, bark thickness, basal area, stand density and tree diameter) and soil properties (pH, organic matter-OM, soil texture, and nutrients). At both sites, the sampling plots were taken from the north and south-slope aspects (NSA and SSA) and from upper and lower-slope positions (USP and LSP) on each site. In general, the results showed that in HVNP, Picea orientalis stands had higher stand age, bark thickness, basal area, and tree diameter, but lower soil pH, OM, nutrients, percent clay and silt content than those in SFSD. Among the stand characteristics, the stand age was positively correlated (r = 0.916) to the mortality rates in HVNP. Besides, Picea orientalis stands on SSA and at USP were more damaged than on NSA and at LSP. In conclusion, the results indicate that forest management practices including thinning, pruning, and cleaning can have a significant favorable influence on Picea orientalis forests to minimize the risk of Ips typographus attacks.
Keywords: Ekoloji; Orman Mühendisliği; Entomoloji